PENGARUH ATRIBUT PRODUK DAN PENETAPAN HARGA TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS ELECTROPLATING PART DI PT. MITRAMETAL PERKASA) - Pramulanto, Himawan (JURNAL LENTERA BISNIS, 2018)
ABSTRACT The purpose of this research was to obtain empirical evidence and found the clarity of the phenomenon  as well  as  conclusions about the effect of  two  variables  for purchase decision  on  PT. Mitrametal Perkasa’s electroplating part.The research was expected to contribute of economics development and marketing management.This research was conducted by using descriptive and verificative methods, are collecting, presenting, analyzing and testing hypotheses, making conclusions and suggestions.From the analysis of research data, obtained the following conclusions: Product attributes of electroplating products at PT. Mitrametal Perkasa have been on high criteria. Pricing of PT. Mitrametal Perkasa’s electroplating products have been on middle criteria. Purchase decision of electroplating products at PT. Mitrametal Perkasa have been on high criteria. The relationship between product attributes with pricing at very strong level and has correlation coefficient 0.844. The partial effect of attributes products to purchase decision has value 43.3%. The partial effect of pricing to purchase decision has value 33%. The simultaneous effect of product attributes and pricing to the purchase decision has value 76.3%.From these results, that variable product attributes and pricing significantly influence to the purchase decision on PT. Mitrametal Perkasa’s electroplating products. Furthermore, for sustainability to improve and optimize these variables, PT. Mitrametal Perkasa was expected to create internal and external continues improvement programs periodically. Keywords: product attributes, pricing, purchase decision